What Explains the Rise in Executive Pay in Germany? A Panel Data Analysis for 1977–20091. (3rd December 2015) - Fabbri, Francesca; Marin, Dalia
Abstract: Executive compensation in Germany has become highly controversial since Vodafone's hostile takeover of Mannesmann in 2000. It has again been in the spotlight since the outbreak of the 2008–2009 global financial crisis. Using a unique panel dataset of the 500 largest firms in Germany in the period 1977–2009, we find that executives tend to be rewarded when the sector is doing well rather than the firm they work for. Furthermore, we find that CEO pay and the demand for managers increases in Germany in difficult times when the typical firm size shrinks. Finally, domestic and global competition for managers appear to contribute to the rise in executive pay.